ANALYSIS OF THE LATEST DEPOSITS TO IDENTIFY THE CONDITIONS OF THEIR FORMATION: (on the example of loose rocks of the Aghstev River basin and the northern slope of the Aragats massif) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The article analyzes the differences in the granulometric composition of fine-grained aggregate (the content of individual fractions, their ratios, gravel content, etc.), as well as the chemical composition and a number of calculated geochemical coefficients of different genetic types of loose rocks. There is a good informative value of the obtained data for identifying the dynamic and climatic conditions of the environment of their formation.
Keywords: channel facies; eluvium; geochemical factor; granulometric composition; moraine; weathering crust